Social Criticism in The Novel “Teruslah Bodoh, Jangan Pintar” by Tere Liye (Sociological Study of Literature) - Ramadani Khusnul Khotimah1; Haris Supratno (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to analyze social criticism in the novel "Teruslah Bodoh Jangan Pintar" by Tere Liye. Specifically, this study attempts to (1) identify the forms of social criticism contained in the novel, (2) understand the process of social criticism in the context of the story, and (3) examine the benefits of social criticism for society, as reflected in the novel. This study uses a descriptive qualitative method with a sociological literary approach and Abrams' mimetic theory to analyze social criticism in the novel "Teruslah Bodoh Jangan Pintar" by Tere Liye. Research data in the form of quotations and dialogues in the novel are analyzed repeatedly to identify the forms of social criticism contained therein. The results of the study show that this novel contains 54 quotations of social criticism covering various aspects of people's lives, such as economics (17 quotations), politics (14 quotations), the environment (11 quotations), and human rights (12 quotations). This social criticism aims to reveal injustice and inequality in society, as well as encourage change for the better. This study concludes that the novel "Teruslah Bodoh Jangan Pintar" by Tere Liye provides benefits for readers to think critically, develop empathy, and be inspired to make social changes.